Ssr Based Population Bottleneck Studies On Coconut Accessions From South Peninsular India - SHALINI PRABHU,; NASARUOLLA PIRANY,; D THEERTHA PRASAD, (International Journal of Pharma and Bio Sciences, 2015)
The fate of alleles after population bottleneck is important for studying the genetic variability of population. For conducting this study, samples from three coconut populations with varied yield traits were collected from different agro climatic regions of south peninsular India. SSR analysis was carried out using thirty- two primer pairs to evaluate genetic variation. Using the software program BOTTLENECK, fluctuations in the population sizes have been identified by detecting the deviations from mutation drift equilibrium. Three well known microsatellite mutation models SMM, TPM and IAM have been used to assess the genetic bottleneck. Three statistical tests - sign test, standardized difference test and wilcox rank test were performed for each mutation model. The results revealed that high yielding and medium yielding populations showed heterozygosity excess, as most of the DH/SD values were positive under IAM, TPM and SMM. However low yielding population showed a heterozygosity deficiency. This clearly shows that the high and medium yielding coconut populations experience genetic bottleneck, however the low yielding population seems to be undergoing rapid population expansion.